2011
DOI: 10.1245/s10434-011-1658-7
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between Tumor Proliferative Activity, Leucocyte and Macrophage Infiltration, Systemic Inflammatory Response, and Survival in Patients Selected for Potentially Curative Resection for Gastroesophageal Cancer

Abstract: Tumor proliferation rate and local and systemic inflammatory responses are important predictors of survival, albeit in a heterogeneous cohort of patients including esophageal, junctional, and gastric cancers. These scores may be combined with accepted tumor-based factors to improve prediction of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
14
2
Order By: Relevance
“…In this study, in contrast, and combining mGPS 1 and 2 together in view of the low numbers of mGPS ¼ 2, an elevated mGPS score was associated with positive nodal status, and advanced tumor stage, but not independently with survival. In the esophageal and gastric literature, this is discordant with two series from the Glasgow group [4,21] and another consistent series of 100 patients with esophageal carcinoma [22]. In the Glasgow study, Dutta et al [4] examined a cohort of 121 patients undergoing curative surgery for esophago-gastric cancer.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, in contrast, and combining mGPS 1 and 2 together in view of the low numbers of mGPS ¼ 2, an elevated mGPS score was associated with positive nodal status, and advanced tumor stage, but not independently with survival. In the esophageal and gastric literature, this is discordant with two series from the Glasgow group [4,21] and another consistent series of 100 patients with esophageal carcinoma [22]. In the Glasgow study, Dutta et al [4] examined a cohort of 121 patients undergoing curative surgery for esophago-gastric cancer.…”
Section: Discussionmentioning
confidence: 94%
“…[ 14 , 15 ] The degree of macrophage infiltration into the cancer cell nest is also a significant predictor of survival in GC patients. [ 16 – 18 ] IHC findings in this study clearly demonstrate that the density of macrophages in GC tissue is correlated with the degree of clinical stage (especially in the tumor [T] stage) and survival in patients. The current studies also imply that macrophages may play harmful roles in advanced GC.…”
Section: Discussionmentioning
confidence: 53%
“…The improved outcome associated with preserved HLA class I expression is closely related to the presence of a pronounced local inflammatory infiltrate. The relationship between the local inflammatory response and improved outcome in GI cancer has been studied previously (Klintrup et al 2005;Crumley et al 2011). Klintrup et al (2005) demonstrated that a high-grade local inflammatory infiltrate was independently prognostic of improved outcome in patients undergoing surgery for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%